Disease-associated inosine misincorporation into RNA hinders translation. Issue 16 (18th August 2022) - Schroader, Jacob H; Jones, Lindsey A; Meng, Ryan; Shorrock, Hannah K; Richardson, Jared I; Shaughnessy, Sharon M; Lin, Qishan; Begley, Thomas J; Berglund, J Andrew; Fuchs, Gabriele; Handley, Mark T; Reddy, Kaalak
Abstract: Failure to prevent accumulation of the non-canonical nucleotide inosine triphosphate (ITP) by inosine triphosphate pyrophosphatase (ITPase) during nucleotide synthesis results in misincorporation of inosine into RNA and can cause severe and fatal developmental anomalies in humans. While the biochemical activity of ITPase is well understood, the pathogenic basis of ITPase deficiency and the molecular and cellular consequences of ITP misincorporation into RNA remain cryptic. Here, we demonstrate that excess ITP in the nucleotide pool during in vitro transcription results in T7 polymerase-mediated inosine misincorporation in luciferase RNA. In vitro translation of inosine-containing luciferase RNA reduces resulting luciferase activity, which is only partly explained by reduced abundance of the luciferase protein produced. Using Oxford Nanopore Direct RNA sequencing, we reveal inosine misincorporation to be stochastic but biased largely towards misincorporation in place of guanosine, with evidence for misincorporation also in place of cytidine, adenosine and uridine. Inosine misincorporation into RNA is also detected in Itpa -null mouse embryonic heart tissue as an increase in relative variants compared with the wild type using Illumina RNA sequencing. By generating CRISPR/Cas9 rat H9c2 Itpa -null cardiomyoblast cells, we validate a translation defect in cells that accumulate inosine within endogenous RNA. Furthermore, we observe hindered cellular translation of transfected luciferase RNA containing misincorporated inosine in both wild-type and Itpa -null cells. We therefore conclude that inosine misincorporation into RNA perturbs translation, thus providing mechanistic insight linking ITPase deficiency, inosine accumulation and pathogenesis.